Disability-Related Risks Among Women and Girls Who Are Forcibly Displaced from Venezuela - Tiahna Warkentin; Maria Marisol; Adans Bermeo; Susan A. Bartels (Disabilities)
Our study aimed to explore the lived experiences of Venezuelan refugee/migrant women and girls with disabilities to guide humanitarian assistance. The data analysed was part of a larger cross-sectional study whereby refugees and migrants in Ecuador, Peru, and Brazil were asked to share the migration experiences of a Venezuelan woman or girl. The sample for this analysis was drawn from one of the survey questions that asked participants whether the woman/girl in the narrative identified as a person with a disability. Thematic analysis using inductive coding was performed. A total of 126 narratives were included in the final analysis, of which four major themes were identified. Venezuelan refugees and migrants with disabilities described experiences of discrimination, violence, and physical challenges, such as exacerbation of symptoms while in transit. In host countries, refugees and migrants experienced a lack of disability-related accommodations in the workplace and long wait times when trying to obtain healthcare. Since discrimination is a cross-cutting issue, human rights awareness highlighting the dignity of persons with disabilities is imperative. Resources and support for Venezuelan refugee and migrant women and girls with disabilities should aim to create accessible employment opportunities, safe and timely access to medical care, and prioritise violence prevention.